When citizens decide : lessons from citizens' assemblies on electoral reform - Fournier, Patrick. (Oxford University Press, 2011)
Three large-scale democratic experiments have taken place in which groups of randomly selected ordinary citizens were asked to independently design the next electoral system. The lessons drawn from the research are relevant for those interested in political participation, public opinion, deliberation, public policy, and democracy.